ANALISIS PEMBIAYAAN MURABAHAH DI PERBANKAN SYARIAH - YENTI AFRIDA (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The research theme is the concept of the bank in accordance with Islamic economics. The research objective is: to analyze murabaha financing in Islamic banking. Research is the study of literature. The object of research is the banking industry in Indonesia. To ensure that the implementation of murabaha financing to fit this concept, it requires strict supervision of the Sharia Supervisory Board or the National Islamic Council, so murabaha financing as financing belle of Islamic banking can be guarded and not tarnish the image and prestige of Islamic banking so that no impression that the bank sharia is the same as conventional banks.